PENGARUH KOMPLEKSITAS TUGAS, TEKANAN ANGGARAN WAKTU, DAN KOMITMEN ORGANISASI TERHADAP PERILAKU DISFUNGSIONAL AUDITOR PADA KANTOR AKUNTAN PUBLIK DI KOTA SEMARANG - Cornelia Widya Ayu Paramita; Srimindarti, Ceacilia (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
The financial condition of a company is reflected through its financial statements, which can serve as an important tool for decision-making by both internal and external parties. To ensure that these reports are relevant and reliable, they must undergo independent evaluation. This task is carried out by external auditors, or public accountants, who review the reports and verify their compliance and accuracy with applicable standards. However, audit quality is increasingly resulting in a decline in auditors. The purpose of this study is to examine the effect of time budget pressure, task complexity, and organizational commitment on dysfunctional auditor behavior. The type of data is primary data with a sampling technique, namely purposive sampling with a sample of 66 auditors from 29 Public Accounting Firms (KAP) in the city of Semarang. The results of the study obtained were that organizational commitment and task complexity had no effect on dysfunctional auditor behavior. This is inversely proportional to the budget pressure of dysfunctional auditor behavior which affects deadlines. The results of this study have an impression for an auditor, where a responsible attitude is very important to ensure that tasks are completed effectively and time is managed efficiently, in addition to the need to allocate sufficient budget and time for each activity. Keywords : Organizational Commitment, Task Complexity, Auditor Dysfunctional Behavior, Time Budget Pressure.